同向双螺杆挤出机挤出物料的混合特性研究Mixing characteristics of materials extruded by coaxial twin screw extruder - 夏伟杰1，马亮2，张俊1，申春赟1 XIA Weijie1, MA Liang2, ZHANG Jun1, SHEN Chunyun1 (Zhongguo youzhi, 2025)
为了提升同向双螺杆挤出机的物料混合均匀性和挤出效率，研究了不同螺杆结构对物料挤出过程的影响机制。首先，建立了普通螺纹有/无啮合块和凹槽螺纹有/无啮合块4种螺杆结构模型；然后，在网格独立性和计算方法有效性试验验证的基础上，建立了三维内流场数值计算模型；最后，基于Ployflow软件进行数值模拟并分析了流场压力、速度分布，并通过示踪粒子轨迹跟踪法分析了物料停留时间及最大剪切应力等变化规律。结果表明：普通螺杆对物料的混合性能低，挤出效率高；啮合块对于提高最大剪切应力有正向作用，可增加混合性能，但自洁能力降低；螺杆上的凹槽结构可减小轴向速度、增大压力差、提高物料混合性能，但降低了物料受到的最大剪切应力。综上，物料通过具有凹槽和啮合块的螺杆结构能得到更好的混合效果。 To improve the material mixing uniformity and extrusion efficiency of coaxial twin screw extruder, the influence mechanisms of different screw structures on the material extrusion process were investigated. Firstly, the four screw structure models of common thread with/without meshing block and grooved thread with/without meshing block were established; then, a three-dimensional internal flow field numerical calculation model was established on the basis of the experimental verification of the grid independence and the validity of the calculation method; finally, the flow field pressure, velocity distribution were simulated and analyzed based on the numerical simulation of the Ployflow software, and the changing rules of material retention time and maximum shear stress were analyzed by tracer particle trajectory tracking method. The results showed that the common screw had low mixing performance of material and high extrusion efficiency. The meshing block had a positive effect on increasing the maximum shear stress, which could enhance the mixing performance, but reduced the self-cleaning ability. The groove structure on the screw could reduce the axial velocity, increase the pressure difference and improve the mixing performance of material, but it reduced the maximum shear stress. In conclusion, the material can be mixed better through the screw structure with groove and meshing block.